2022
DOI: 10.3390/life12020139
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticle Production by the Cyanobacterium Cyanothece sp.: De Novo Manipulation of Nano-Biosynthesis by Phytohormones

Abstract: Background: Numerous cyanobacteria have the potential to reduce metallic ions to form pure metal nanoparticles in a green biosynthesis process. Aim: To investigate the production capacity of silver nanoparticles by the cyanobacterium Cyanothece sp. and to examine the effect of five different phytohormones, indole acetic acid, kinetin; gibberellic acid; abscisic acid; and methyl jasmonate, on this capacity. Methods: The cyanobacterial strain was grown for 60 days and the harvested cyanobacterium biomass was inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The three samples of biogenic nanosilver showed a strong absorbance peak at 450 nm (Figure 3 and Supplementary Materials, Figures S1 and S2). This is within the range of plasmon resonance that is characteristic of silver nanoparticles [3]. The characteristic plasmon resonance of silver nanoparticles is due to the vibrational modes of electrons based on the size and shape of nanoparticles [17].…”
Section: Uv-visible Spectroscopymentioning
confidence: 71%
See 2 more Smart Citations
“…The three samples of biogenic nanosilver showed a strong absorbance peak at 450 nm (Figure 3 and Supplementary Materials, Figures S1 and S2). This is within the range of plasmon resonance that is characteristic of silver nanoparticles [3]. The characteristic plasmon resonance of silver nanoparticles is due to the vibrational modes of electrons based on the size and shape of nanoparticles [17].…”
Section: Uv-visible Spectroscopymentioning
confidence: 71%
“…Nanoparticles are minute particles of size 10 −9 m whose chemical and physical characteristics are different from bulk particles [1]. Cyanobacteria are wide-spread photosynthetic prokaryotes that represent bio-factories for the production of nanoparticles [2,3]. Cyanobacteria grow rapidly in inexpensive growth media, require only minerals and light energy for growth and can produce nanoparticles without toxic byproducts or energy consumption [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, as phytohormones regulates different plant processes, novel research has proposed the implementation of these compounds to increase the efficiency in the process of NPs biosynthesis. For example ( Mohamed et al., 2022 ), found that the addition of indole acetic acid and kinetin to the cyanobacterium Cyanothece sp provoked a maximum conversion (87.29% and 55.16%, respectively) for the production of Ag NPs, and that methyl jasmonate increased the NPs conversion rate to 90.29%, although nearly all the cyanobacterial cultures died at the end. Although the effect of various nanoparticles on plant growth and development has been extensively investigated, there are still many questions about their action.…”
Section: Agricultural Potential and Plant Effect Of Npsmentioning
confidence: 99%